Unusual Behavior of the Magnetization Reversal Process of Interacting Nanostructures with Wire-Tube Morphology - Escrig-Murua, J (Elsevier B.V., 2020)
We have studied the magnetostatic interactions between two parallel cylindrical nanostructures with wire-tube morphology as a function of their interaxial separation and the magnetic field applied using micromagnetic simulations. We find that the hysteresis curves of the system can exhibit one, two or three Barkhausen jumps as a function of the separation between the nanostructures and the angle at which the external magnetic field is applied, which are related to the reversal of the magnetic moments of certain segments of the nanostructures. In addition, by studying the averages of magnetization we obtain that for angles less than or equal to 60 degrees, the nanostructures reverse their magnetization through the nucleation and propagation of domain walls (vortex for the tube segment and transverse for the wire segment), while for higher angles the nanostructures revert their magnetization by quasi-coherent rotation. © 2019 Elsevier B.V.